Online Television Forums: Interactivity, Access, and Transactional Space - McKay, Susan; Rintel, Sean (The Electronic Journal of Communication / La Revue Electronic de Communication, 2001)
In online television forums hosted by Television Network Websites (TNWs), viewers are invited to interact with both those involved with the television network and/or other viewers/users. This paper is a preliminary investigation of the enormous range of new interactive spaces and practices. Current online television forums in US, UK and Australian TNWs are analyzed in terms of their interactivity and access. The forums are found to allow individuals increased and more immediate access to television products and personalities, the ability to determine their own news values, and the possibility of joining with others as transitory online communities rather than remaining an audience of individuals. While those who gain access and participate must agree to both rules and moderation, some users manage to subvert officially designated purposes or rules. Nevertheless, the provision of online television forums ultimately extends the traditional media sphere.
McKay, S., & Rintel, E.S. 2001. Online Television Forums: Interactivity, Access, and Transactional Space. The Electronic Journal of Communication, 11, (2). Online version is free and best (use Publisher URL)